Ameliorative effect of Fennel (Foeniculum vulgare) essential oil on chlorpyrifos toxicity inCyprinus carpio - Pala, Aysegul; Serdar, Osman; Mise Yonar, Serpil; Yonar, Muhammet Enis (Springer Heidelberg, 2021)
Chlorpyrifos (CPF) is an organophosphate pesticide that is frequently and widely used to control both agricultural and domestic pests worldwide. In this study, the protective effect of Fennel (Foeniculum vulgare) essential oil (FEO) was investigated in carp (Cyprinus carpio) exposed to CPF. The fish were divided into six groups that one control group (no treatment) and five experimental groups (FEO (3ml/100g diet) group, CPF1(0.023 mg/l) group CPF2(0.046 mg/l) group, CPF1(0.023 mg/l) plus FEO (3ml/100g diet) group, CPF2(0.046 mg/l) plus FEO (3ml/100g diet) group). Blood and tissue (liver, kidney, gill, and brain) samples were taken from the fish at the end of 14 days of application. Hemoglobin (Hb) level, nitoblue tetrazolium (NBT) activity, and total immunoglobulin (TI) level were measured in blood samples of fish. Acetylcholinesterase (AChE) activity was determined in brain tissue while malondialdehyde (MDA) level, reduced glutathione (GSH) level, catalase (CAT), and glutathione peroxidase (GPx) activity were determined in liver, kidney, and gill tissues. The results showed that there was a significant decrease in Hb level, NBT activity, and TI levels in CPF-treated fish compared to the control group. In addition, increased in MDA levels and significant decreases in GSH level, AChE, CAT, and GPx activities were observed in CPF-treated groups. However, FEO-treated was showed a significant improvement in all parameters except AChE activity compared to CPF groups. These study findings showed that FEO could improve CPF-induced toxicity inC. carpio, except inhibition of AChE activity.
Keywords: Antioxidant; Chlorpyrifos; Fish; Fennel; Oxidative stress; Immunology